Pay Transparency across Countries and Legal Systems - Martha Ceballos; Annick Masselot; Richard Watt (CESifo Forum, 2022)
Women's participation in the labor market is increasing and the gender pay gap is narrowing worldwide. Yet how fast and how profound the development takes place varies from one country to another. In Europe, there is still controversy as to whether the regulations introduced on pay transparency have made an effective contribution to reducing these differences. While more women are available on the labor market, their wage in some segments has not grown to the same extent. However, the discussion about the gender pay gap has broadened and become more differentiated: the aspect of the natural gender gap has been added, to which countries would gravitate in absence of legal regulations designed to reduce this gap. And there is a new discussion about the differences in pension payments between men and women. This edition of the CESifo Forum offers country-specific experiences as well as insights into these critical policy issues in selected countries.
Keywords: 330